SEMIOTIC STUDY OF THE FILM “AKU PENGGAK MIMPI” AND ITS RELEVANCE AS AN INDONESIAN LANGUAGE TEACHING MATERIAL IN SCHOOLS - Bela Yosika Oktavia; Dalman; Saleh Faharudin (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to analyze the film “Aku Penggerak Mimpi” using a semiotic approach and evaluate its relevance as Indonesian language teaching material in schools. Roland Barthes’ semiotic approach is used to explore the denotative, connotative, and mythical meanings contained in the film. This study also uses a qualitative descriptive method to understand how this film can support Indonesian language learning, especially in improving students’ analytical skills towards narratives, morals, and culture conveyed through visual media. The results of the study show that this film contains various signs, symbols, and meanings that are relevant to learning. The signs found not only depict struggles and hopes but also reflect moral values that are important to students, such as the spirit of hard work, the importance of education, and family warmth. The relevance of this film to Indonesian language teaching materials can be seen from its ability to teach students to analyze narrative texts visually and contextually, as well as hone students’ understanding of the socio-cultural context reflected in the story. Thus, this film has great potential as an innovative teaching material that motivates students to think critically and creatively. Educators are advised to utilize this film as part of a learning strategy that supports the Indonesian language curriculum and enhances students’ learning experiences. Keywords : Semiotics, Teaching Materials, Indonesian, Film, Education.